Legal issues arising from minority shareholdes’ remedies in Malaysia and United Kingdom - Aishah Hj Bidin (Fakulti Undang - Undang, 2003)

(untitled)
The rules surrounding the standing, pleadings and proof of corporate litigation are notoriously convoluted. Towering over the area stands the legacy of the rule in Foss v, Harbottle which forms a major precedent in this area of law in Malaysia. The shareholders whether he has majority, substantial or minority interest is really concerned with the issue of managerial accountability and with the enforcement of a corporate right. However, there are many persisting setbacks and limitations surrounding the rule in Foss v. Harbottle. The article will make an attempt to highlight the legal issues arising from the provisions governing the shareholders remedies in Malaysia and compare with the legal position in United Kingdom incorporating the latest effort by the UK Law Commission Consultative Paper No. 142 on Shareholder remedies. Finally the paper will also proposed the possibility of introducing a statutory derivative action in Malaysia and the legal ramifications arising from such proposal